Health-Related Quality of Life in perimenopausal women with PCOS - Maria Forslund; Kerstin Landin-Wilhelmsen; Emily Krantz; Penelope Trimpou; Johanna Schmidt; Mats Brännström; Eva Dahlgren (Clinical and Experimental Obstetrics & Gynecology)
Background: Several studies have shown that younger women with polycystic ovary syndrome (PCOS) have decreased Health-Related Quality of Life (HRQoL) compared with women in general. Method: In this study peri- and postmenopausal women previously diagnosed with PCOS (n = 27) were compared with randomly selected, age-matched controls (n = 94). Mean age of the study participants was 52 years. Structured interviews and Short Form (SF)-36 questionnaires were used. Results: No differences in SF-36 scores were found, median for the physical summary score was 54 vs. 57, for women with PCOS and controls, respectively; and 53 vs. 53 for the mental summary score, with no differences in any of the eight dimensions of HRQoL. There were no significant difference in prevalence of depression and/or anxiety. The use of drugs for mood disorders was 22% in both groups. Conclusion: PCOS women of peri- and postmenopausal ages had similar HRQoL compared with age-matched controls.